Efeitos da atividade física na melhora do sono de idosos - Damacena, Weberson Gonçalves; Oliveira, Evandro Salvador Alves de; Oliveira, Evandro Salvador Alves de; Lopes, Lorena Cristina Curado (International Journal of Movement Science and Rehabilitation, 2020)
This study aims to analyze the main effects of physical activity in improving sleep in the elderly. The article also seeks to identify the main sleep-related disorders; to verify the possible implications that the lack of sleep causes to the health of the individual; as well as presenting recommendations for physical activities to the elderly targeting the improvement of sleep. It is a bibliographical and documentary research, with a qualitative approach, in which scientific works selected from the object of study were used: physical activity and sleep of the elderly. The conclusions point out that the practice of physical activity significantly improves the sleep pattern in elderly people, since the regularity of physical activity plays a fundamental role in the lives of the elderly, especially in terms of physiological changes. Physical activity acts in the prevention and control of chronic non-communicable diseases, since exercise can help in the treatment and prevention of some disorders of the sleep-wake cycle, by decreasing sleep fragmentation, or by increasing slow wave sleep. It was identified that A. F. helps to improve mobility, exercising significant importance in terms of functional and psychological capacity, mainly by improving the quality of life during the aging process.